Novel calcium-based adsorbent as well as preparation method and application thereof
By doping calcium carbide slag with MgO and FeC6H5O and using biomass solution as templates, a new type of calcium-based adsorbent was prepared, which solved the problems of easy sintering, poor stability and poor solar energy absorption capacity of existing calcium-based adsorbents, and achieved higher energy storage performance and cycle stability.
Patent Information
- Application Number
- CN202411869510.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
The existing calcium-based adsorbents have problems such as sintering, poor stability and poor solar energy absorption capacity, which limits their application in third-generation photothermal power plants.
A new calcium-based adsorbent was prepared by mixing calcium carbide slag with MgO powder and FeC6H5O powder and adding biomass solution as a template. This method increases the optical absorption and cyclic stability of the material by doping MgO and FeC6H5O, and improves the porosity and CO2 adsorption capacity of the material through biomass templates.
The prepared new calcium-based adsorbent exhibits higher stability and stronger solar energy absorption capacity during high-temperature cycles, significantly improving its energy storage performance and cycle stability in thermochemical energy storage systems.
Smart Images

Figure CN119657065A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of calcium-based adsorbents, and in particular to a novel calcium-based adsorbent and a preparation method and application thereof. Background Art
[0002] The fossil fuel energy currently used the most in the world is not only limited but also produces a certain amount of heat and pollution. Solar energy is an abundant renewable resource. Because it is safer, more environmentally friendly and low-cost, it can replace fossil fuels and other energy sources. Its large-scale development and utilization can effectively reduce CO2 emissions and solve the energy crisis of fossil fuels. However, due to the variability of weather conditions, there are certain intermittent and volatile problems in the supply of solar energy, and heat cannot be supplied continuously and stably. By combining concentrated solar power (CSP) systems with thermochemical energy storage (TCES) technology to convert solar energy into thermal energy and then into electrical energy, the volatility and intermittency of solar energy can be effectively solved. At present, there are three main categories of thermal energy storage: thermochemical heat storage (TCES), latent heat (LHS) and sensible heat (SES). Compared with LHS and SES, TCES has attracted widespread attention for its advantages such as wide temperature range, long storage time, high energy storage density and low heat loss. The third generation of CSP plants pursues higher operating temperatures (>700℃) and higher power generation efficiency. Thermochemical energy storage systems based on calcium cycle (CaL) meet the requirements of the third generation of CSP plants. Among various thermochemical energy storage materials, carbonate CaCO3 / CaO is one of the most promising materials in concentrated solar power (CSP) technology. The main advantages of CaCO3 / CaO as a thermochemical energy storage material include abundant natural reserves, environmental friendliness, low cost, high energy storage density, high safety, and fast energy storage and release kinetics. As a thermochemical energy storage material, the storage and release of thermal energy of CaCO3 / CaO is completed through the following reversible reaction (Formula 1):
[0003]
[0004] In addition to the CaCO3 / CaO system, the Ca(OH)2 / CaO system also brings certain difficulties to industrial applications due to its low operating temperature, water vapor condensation, particle agglomeration and the negative influence of certain CO2 in the air. The redox system of metal oxides, but its high cost and toxicity also limit its large-scale application in industry. The CaCO3 / CaO system is more suitable for the TCES system. The calcium cycle (CaL) thermochemical energy storage system will be widely used in the third-generation solar thermal power station. The calcium-based system has severe sintering and poor solar energy absorption capacity. Therefore, it is imperative to synthesize a calcium-based adsorbent that is sinter-resistant and stable.
[0005] Calcium precursor is the main component of calcium-based adsorbent, contains CaCO / CaO system has a lot of materials, and some calcium-containing wastes such as dolomite, red mud, carbide slag, egg shells can be used as calcium precursor. And carbide slag wherein is a kind of industrial waste with high calcium content generated in a large number, and annual generation can reach 900,000-1.14 million tons. The main component of carbide slag is CaO, which can be used as the active material of calcium circulation and absorbs CO , so the present invention uses carbide slag as calcium precursor, but only uses carbide slag as energy storage material and still has the problems of easy sintering, poor stability and poor solar absorption capacity.
[0006] Therefore, those skilled in the art provide a novel calcium-based adsorbent and a preparation method thereof to solve the above-mentioned technical problems. Summary of the invention
[0007] The purpose of the present invention is to provide a novel calcium-based adsorbent and a preparation method and application thereof, so as to solve the technical problems of the calcium-based adsorbent in the prior art, such as easy sintering, poor stability and poor solar energy absorption capacity.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a novel calcium-based adsorbent, comprising the following steps:
[0010] (1) drying the carbide slag in an oven at 80°C for 12 h to remove moisture from the sample, grinding the dried carbide slag into powder, and calcining it in a muffle furnace at 800°C for 1 h to obtain carbide slag powder;
[0011] (2) Carbide slag powder, MgO powder and FeC6H5O powder were mixed and added into a ball mill, and ethanol (as a dispersant) was added for ball milling to fully mix the powders to obtain a sample;
[0012] (3) Prepare a biomass solution and add the sample, mix on a magnetic stirrer, and then place in a convection oven at 80°C for 20 h;
[0013] (4) After drying, the mixture was ground into powder and calcined in a muffle furnace at 800°C for 1 h under air conditions;
[0014] (5) The calcined sample was placed in a tubular furnace and pre-calcined at 800°C for 20 min under N2 conditions to obtain a calcium-based adsorbent.
[0015] Furthermore, in step (2), the ball mill rotates at a speed of 300 r / min for 30-40 min during ball milling.
[0016] Furthermore, in step (2), the mass ratio of the carbide slag powder, MgO powder and FeC6H5O powder is 100:5:5.
[0017] Furthermore, in step (3), the concentration of the biomass solution is 5%-10%.
[0018] Furthermore, the biomass solution includes a soluble starch solution or a methylcellulose solution.
[0019] Furthermore, in step (3), during the stirring process of the magnetic stirrer, stirring is first performed at room temperature for 1.5 hours to allow the sample and the biomass solution to be fully mixed, and then heated and stirred to a semi-dry mixed state.
[0020] In a second aspect, the present invention provides a novel calcium-based adsorbent prepared by a method for preparing a novel calcium-based adsorbent.
[0021] In a third aspect, the present invention provides the application of a novel calcium-based adsorbent in solar thermochemical energy storage.
[0022] Furthermore, the calcium-based adsorbent is used to slow down sintering and enhance solar energy absorption capacity during the calcium circulation process, and is suitable for the thermochemical energy storage system of the third-generation solar thermal power station.
[0023] Based on the above technical solution, the embodiments of the present invention can at least produce the following technical effects:
[0024] (1) The preparation method of the novel calcium-based adsorbent provided by the present invention is dedicated to developing a green, economical and efficient calcium-based adsorbent using waste materials and some biomass. After adding FeC6H5O, the dark substances Fe2O3 and Ca2Fe2O5 generated at high temperature with CaO increase the optical absorption rate of S5-CSMg5Fe5 and MC5-CSMg5Fe5. After MgO and FeC6H5O are added at the same time, the Xn, Eg,n and cycle stability of S5-CSMg5Fe5 and MC5-CSMg5Fe5 during the carbonation / calcination cycle are increased. On this basis, after adding the biomass template, S5-CSMg5Fe5 and MC5-CSMg5Fe5 initially have more mesopores and macropores, which is attributed to the formation of a large number of pores during the combustion process after the addition of the biomass template, which improves the CO2 adsorption capacity. After 20 carbonation / calcination cycles, the specific surface area and pore volume of S5-CSMg5Fe5 and MC5-CSMg5Fe5 also increased. Since MgO played a supporting structure role during the cycle, the number of oxygen vacancies also increased significantly, accelerating the reaction rate.
[0025] (2) The novel calcium-based adsorbent and its application provided by the present invention can make better use of solid waste and effectively utilize biomass materials to provide certain technical support for energy storage materials. It has high energy storage performance and the ability to directly utilize solar energy, and has good application prospects in the third-generation solar thermal power station. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0027] Figure 1 are SEM images of different calcium-based adsorbents of the present invention; (a) is fresh CS, (b) is CS after 20 cycles, (c) is fresh S5-CSMg5Fe5, (d) is S5-CSMg5Fe5 after 20 cycles, (e) is fresh MC5-CSMg5Fe5, and (f) is MC5-CSMg5Fe5 after 20 cycles;
[0028] Figure 2 is the weight loss curve of the soluble starch and methyl cellulose of the present invention;
[0029] Figure 3 Comparison of the effects of single doping of FeC6H5O and double doping of MgO and FeC6H5O on energy storage performance of carbide slag of the present invention
[0030] Figure 4 It is the energy storage performance of the calcium-based adsorbent with different biomass and different concentrations of biomass template added in the present invention;
[0031] Figure 5 The effects of different MgO and FeC6H5O doping contents in CS of the present invention on energy storage performance, (a) is a 5% methyl cellulose solution, (b) is a 5% soluble starch solution;
[0032] Figure 6 (a), (b), and (c) are the changes in the mass of CS, S5-CSMg5Fe5, and MC5-CSMg5Fe5 over time, respectively; (d) is the carbonation conversion rate and energy storage density of the calcium-based composite material in multiple carbonation / calcination cycles;
[0033] Figure 7 is the XRD spectra of CS, S5-CSMg5Fe5 and MC5-CSMg5Fe5 of the present invention;
[0034] Figure 8 are (a) pore volume and pore diameter, and (b) N2 adsorption-desorption isotherms of CS, S5-CSMg5Fe5 and MC5-CSMg5Fe5 before and after 20 carbonation / calcination cycles of the present invention;
[0035] Fig. 9 The following are (a) XPS wide scan spectra, (b) XPS spectra of Fe2p, (c) XPS spectra of Mg 1s, and (d) XPS spectra of O 1s of CS, S5-CSMg5Fe5 and MC5-CSMg5Fe5 of the present invention;
[0036] Fig.10 These are the EDS mapping images of the elements Ca, Mg, O and Fe in the calcium-based adsorbent of the present invention, (a) is CS, (b) is S5-CSMg5Fe5, and (c) is MC5-CSMg5Fe5;
[0037] Fig.11 is the absorption spectrum of the sample of the present invention. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0039] In the present embodiment, industrial waste carbide slag (from Ningxia Jiyuan Juntai New Material Technology Co., Ltd.), soluble starch (from Tianjin Zhiyuan Chemical Reagent Co., Ltd.) and methyl cellulose (from Aladdin), MgO (from Tianjin Fengchuan Chemical Reagent Technology Co., Ltd.), FeC6H5O (from Xilong Science Co., Ltd.), ethanol (from Guangdong Guanghua Science and Technology Co., Ltd.) are used, and deionized water is used for solution preparation. The chemical composition and composition of carbide slag are shown in Table 1 (X-ray fluorescence (XRF) data), and its main component is CaO.
[0040] Table 1 Main chemical components and composition of carbide slag
[0041] Element CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO <![CDATA[Fe2O3]]> Other LOI Content (wt%) 79.8 2.09 0.656 0.258 0.256 0.94 16
[0042] 1. Preparation of adsorbent
[0043] The process of doping carbide slag is as follows: Figure 1 As shown. First, the carbide slag was dried in an oven at 80°C for 12 hours to remove the moisture in the sample, and the dried carbide slag was ground into powder and calcined in a muffle furnace at 800°C for 1 hour. Carbide slag powder, MgO powder and FeC6H5O powder were added to a ball mill according to different mass ratios and ethanol (as a dispersant) was added for ball milling to fully mix the sample. Biomass solutions (soluble starch solution / methyl cellulose solution) of different concentrations (5%, 10%) were prepared in a beaker and added to the ball-milled sample, and mixed on a magnetic stirrer. First, it was stirred at room temperature for 1.5 hours to fully mix the sample and the template material, and then heated and stirred to a semi-dry mixed state, placed in a convection oven at 80°C for 20 hours, and then ground into powder after drying and calcined at 800°C in air in a muffle furnace for 1 hour. The calcined carbide slag and the prepared sample were placed in a tubular furnace and pre-calcined at 800°C for 20 minutes under N2 conditions. The obtained sample is called a calcium-based adsorbent. The composition and nomenclature of the doped carbide slag are shown in Table 2. The added carbide slag is 100, and the remaining substances are added in proportion to the carbide slag; S represents soluble starch, MC represents methyl cellulose, and a, b, c and d represent the concentration of the biomass template, the mass percentage of MgO, the mass percentage of FeC6H5O and the number of cycles, respectively. For example, the calcium-based adsorbent formed by CS doped with 5% soluble starch solution, 5% mass ratio MgO, and 5% mass ratio FeC6H5O is named S5-CSMg5Fe5-20 after 20 carbonation / calcination.
[0044] Table 2 Composition and nomenclature of calcium-based adsorbents doped with carbide slag
[0045]
[0046] 2. Carbonation / Calcination Cycle Experiment
[0047] A cyclic experiment was carried out on a double fixed bed reactor consisting of a carbonation reactor and a calcination reactor. The specific process is: first, 0.5g of the calcium-based adsorbent sample is evenly spread in a porcelain boat, sent into the carbonation reactor, and kept at 650°C for 20 minutes under a pure CO2 atmosphere. When the temperature of the carbonation reactor drops to room temperature, the porcelain boat and the sample are weighed using a precision electronic balance. Then, the porcelain boat and the sample are sent into the calcination reactor and kept at 850°C for 20 minutes under a pure N2 atmosphere. When the temperature of the calcination reactor drops to room temperature, they are weighed again. Repeat the above steps until the carbonation / calcination cycle experiment is completed. During the cyclic experiment, the gas flow rate is 100ml / min. In this study, the energy storage performance of the calcium-based composite material is characterized by carbonation conversion rate and energy storage density. The carbonation conversion rate formula and energy storage density formula are defined as Equation 2 and Equation 3, respectively:
[0048]
[0049] In the formula, n represents the number of energy storage cycles, m0, m carb,n and m cal,n represent the mass of the sample after pre-calcination, the nth carbonation and the nth calcination, respectively, M CaO (56 g / mol) and MCO2 (44 g / mol) are the molecular weights of CaO and CO2, respectively. ΔH (178 kJ / mol) is the standard enthalpy of calcination reaction. n (%) is the carbonation conversion rate, E g,n (kJ / kg) is the energy storage density.
[0050] The sample carbonation / calcination cycle experiment and the carbonation reaction kinetics test were carried out in a synchronous thermal analyzer (STA449F5, produced by NETZSCH, Germany). The experimental process is: the pre-calcined sample is placed in an alumina crucible, heated to 650°C at a rate of 20°C / min under N2 atmosphere, switched to CO2 atmosphere and maintained for 90 minutes, then switched to N2 and heated to 850°C and maintained for 10 minutes, then cooled to 650°C at a rate of 20°C / min under N2 atmosphere, and the above carbonation and calcination process is repeated to test the cyclic CO2 absorption capacity of the calcium-based adsorbent. The results of the first and tenth cycles are used for kinetic studies.
[0051] 3. Characterization of adsorbent
[0052] In order to clarify the relationship between the structure and properties of the materials, the phase composition of the calcium-based adsorbent samples was analyzed by X-ray diffraction (XRD; SmartlabSE, Japan), with the scanning rate set at 10° / min and the scanning range of 10–80° (2θ). The chemical composition and electronic valence state of each component in the sample were analyzed by X-ray photoelectron spectroscopy (XPS; ESCALAB Xi+). The specific surface area, pore volume, and average pore size of the absorbent were obtained by isotherm calculation using the Brunauer–Emmett–Teller (BET; ASAP 2460, Micromeritics) and Barret–Joyner–Halenda (BJH; ASAP 2460, Micromeritics) methods. The samples were completely degassed at 200 °C before the N2 adsorption and desorption processes. In order to further understand the morphology and structure of the absorbent, the microscopic morphology of different calcium-based adsorbents was characterized by scanning electron microscopy (FE-SEM; SYGMA500, Germany), and the microstructure of the absorbent was observed at different magnifications. The element distribution of Ca, O, Mg, and Fe on the surface of the composite material was analyzed by energy dispersive spectrometer (EDS). The cyclic CO2 absorption capacity of the calcium-based adsorbent and the carbonation reaction kinetics were tested by synchronous thermal analyzer (TGA; STA449F5, Germany). Finally, the absorbance characteristics of the samples were measured at a wavelength of 300-1200nm by ultraviolet (UV) spectrophotometry (PerkinElmer Lambda750S).
[0053] IV. Conclusion
[0054] 1. Characterization of biomass template
[0055] Figure 2 The weight loss curves of soluble starch and methyl cellulose as biomass templates in the TGA analysis report are shown, with a temperature range of 50-800°C. The curve trend in the figure shows that the mass of soluble starch and methyl cellulose templates decreases rapidly with the increase of temperature after 250°C, and the biomass template burns rapidly in this process. When the temperature reaches 475°C, the weight loss curves of the two biomasses remain constant, indicating that at this time only a small amount of carbon skeleton remains to play a supporting role in both, and the continued increase in temperature will not affect the mass of the skeleton. Therefore, soluble starch and methyl cellulose were doped into carbide slag as biomass templates for subsequent research.
[0056] 2. Cyclic heat storage experiment of calcium-based adsorbent
[0057] 2.1 Effect of doping substances on the energy storage performance of calcium-based adsorbents
[0058] Figure 3This is a comparison of the effects of carbide slag doped with FeC6H5O alone and doped with MgO and FeC6H5O on energy storage performance. As can be seen from the figure, with the increase of the cycle test, the carbonation conversion rate and energy storage density of the CS adsorbent decrease rapidly. The carbonation conversion rate of the CS adsorbent is 74.22% in the first cycle, and the carbonation conversion rate is only 39.28% after five cycles. The carbonation conversion rate of the calcium-based adsorbents CSFe5, CSFe10 and CSFe15 doped with FeC6H5O alone is about 45% after five cycles, which is 5.72% higher than the Xn of CS. This is because the material modified by doping FeC6H5O burns and releases citrate in the high-temperature cycle, generating certain pores, and the iron element reacts with CaO to generate Ca2Fe2O5 ( Figure 7 ), and although the dark Ca2Fe2O5 material can increase the absorbance of the calcium-based adsorbent, it has a negative effect on the anti-sintering of the calcium-based adsorbent. Therefore, it is considered to double-dope the CS doped with FeC6H5O, and add an inert material MgO with a high Tammann temperature as a supporting structure to inhibit the aggregation of CaO particles during the cycle. When double-doping, two mass ratios (100:5 and 100:10) with higher Xn when single-doped FeC6H5O are selected. After five cycles, the carbonation conversion rate of CSMg5Fe5, CSMg10Fe5 and CSMg10Fe10 in the calcium-based adsorbent doped with MgO and FeC6H5O is about 50%, which is 5% higher than the single-doped Xn and 10.72% higher than the Xn of CS. After adding MgO, the carbonation conversion rate becomes more stable, because MgO is an inert oxide, which can provide structural support for the synthesized calcium-based adsorbent, thereby inhibiting the sintering of the calcium-based adsorbent during the high-temperature carbonation / calcination cycle. At the same time, MgO can weaken the mutual aggregation between the regenerated CaO particles during the calcination process. However, the carbonation conversion rate of the first cycle of dual doping is lower than that of single doping. The reason is that after adding MgO, the mass fraction of MgO increases and the CaO content in the sample decreases, so the Xn and Eg,n of the first cycle decrease. In short, in the cycle experiment, dual doping has a higher and more stable carbonation conversion rate and energy storage density than single doping.
[0059] 2.2 Effect of biomass template doping on energy storage performance
[0060] In order to explore the optimal concentration of biomass template, five carbonation / calcination cycle experiments were conducted. Figure 4The carbonation conversion rate and energy storage density of calcium-based adsorbents added with 5% and 10% soluble starch solutions and 5% and 10% methylcellulose solutions. As can be seen from the figure, the Xn and Eg,n of the calcium-based adsorbents added with 5% soluble starch and 5% methylcellulose are significantly higher with the increase of the number of cycles, among which S5-CSMg5Fe5, S5-CSMg10Fe5 and MC5-CSMg5Fe5 have higher Xn than CS in the fifth cycle. This result confirms that the addition of biomass templates can improve the energy storage efficiency of materials. However, when the concentration of biomass templates increases to 10%, the carbonation conversion rate of the synthesized calcium-based adsorbent is low. The reason may be that the ash carbon skeleton content produced after the rapid combustion of the template is high, which blocks some pores. In subsequent studies, the concentrations of the doped biomass template soluble starch solution and methylcellulose solution were 5%.
[0061] 2.3 Effect of MgO and FeC6H5O doping amounts on energy storage performance
[0062] like Figure 5 As shown in Figure (a), the effect of different MgO and FeC6H5O doping amounts on carbonation conversion rate and energy storage density under the condition of CS doped with 5% soluble starch solution template is described. It can be seen that all calcium-based adsorbents show better energy storage performance than CS. The Xn of CS samples is constantly decreasing, especially in the first few cycles, from 74.22% of X1 to Xn. 10 31.88% of the total Xn of MC5-CSMg5Fe5 and MC5-CSMg10Fe5 after the third cycle. Among them, S5-CSMg5Fe5 and S5-CSMg10Fe5 showed better stability. Figure (b) describes the effect of different MgO and FeC6H5O doping amounts on carbonation conversion rate and energy storage density under the condition of CS doped with 5% methyl cellulose solution template. Compared with the calcium-based adsorbent doped with soluble starch template, the Xn of the calcium-based adsorbent doped with methyl cellulose fluctuated greatly in 10 cycles, among which MC5-CSMg5Fe5 and MC5-CSMg10Fe5 had a large increase in Xn in the fourth cycle. The Xn of all calcium-based adsorbents in the first cycle in Figures (a) and (b) was less than that of CS. The reason may be that after adding MgO, FeC6H5O and biomass template, the CaO content in the sample decreased, resulting in a decrease in Xn.
[0063] 2.4 Effect of synthetic calcium-based composites on cyclic stability
[0064] After cycling in a dual fixed-bed reactor, four better samples were selected and subjected to 20 carbonation / calcination cycles in a TG to better observe their cycling stability. Figure 6(ac) depict the weight loss / gain curves of the calcium-based adsorbents obtained by thermogravimetric analysis versus reaction time. Due to the different compositions of the calcium-based adsorbent materials, their weight change trends vary greatly. Figure (d) shows the carbonation conversion rate and energy storage density of the calcium-based adsorbent materials during 20 carbonation / calcination cycles. It can be seen that the Xn of CS decreases rapidly, from 79.78% to 46.7%, with a decay rate of 33.08%, while the decay rates of S5-CSMg5Fe5, S5-CSMg10Fe5, MC5-CSMg5Fe5 and MC5-CSMg10Fe5 are only 20.23%, 18.4%, 16.58% and 13.56%, respectively, which are all lower than the decay rate of Xn of CS, showing better cycle stability. MC5-CSMg5Fe5 also exhibits the phenomenon of "self-activation". Among them, after 20 carbonation / calcination cycles, the Eg,n of S5-CSMg5Fe5 and MC5-CSMg5Fe5 are still relatively high, which are 1602.95KJ / kg and 1643.01KJ / kg respectively.
[0065] 3. Microscopic characteristics of synthetic calcium-based composite materials
[0066] 3.1 XRD analysis
[0067] The phase composition of different calcium-based adsorbents was analyzed by X-ray diffraction. Figure 7 As shown, all prepared calcium-based adsorbents show high-intensity CaO peaks, and the XRD patterns presented prove the crystal structure of the prepared adsorbents. As can be seen from the figure, there are still some differences between the peaks of CS and S5-CSMg5Fe5, MC5-CSMg5Fe5. Among them, the peaks of MgO, MgFe2O4, Fe2O3 and Ca2Fe2O5 are also added in the S5-CSMg5Fe5 and MC5-CSMg5Fe5 samples. The reason for the increase in the peak width of the CaO main peak is that the CaO grain size has decreased. The diffraction peaks of Ca2Fe2O5 and MgFe2O4 are observed, which are the result of the reaction of active CaO with the doped FeC6H5O and MgO materials. The Ca2Fe2O5 crystal phase is an inactive calcium phase, which cannot absorb a large amount of carbon dioxide, and its poor sintering resistance will lead to a decrease in the service life of the synthesized calcium-based adsorbent. Therefore, biomass templates, Mg and Fe elements are co-doped to overcome the shortcomings of single Fe doping to prepare dark CaO-based composite materials.
[0068] 3.2 BET and BJH analysis
[0069] The specific surface area was determined by the BET method, and the pore volume and pore size were determined by the BJH method. Table 3 shows the specific surface area, pore volume and pore size of CS and the synthesized calcium-based adsorbent before and after 20 cycles. The specific surface area, pore volume and pore size of fresh CS were 16.9891 m 2 / g, 0.113cm 3 / g, 23.8568nm. After 20 cycles of carbonation / calcination, due to the large sintering and agglomeration between CS particles, its specific surface area and pore volume decayed, falling to 80.33% and 61.59% of the original, respectively. Although the specific surface area and pore volume of fresh S5-CSMg5Fe5 and MC5-CSMg5Fe5 are smaller than those of CS, after 20 cycles, the specific surface area and pore volume of S5-CSMg5Fe5 are 1.21 and 1.20 times that of CS, and the specific surface area and pore volume of MC5-CSMg5Fe5 are 1.29 and 1.55 times that of CS. During the carbonation / calcination cycle, the larger specific surface area can increase the contact area between CO2 and the active sites, thereby accelerating the reaction rate and promoting the energy storage of calcium-based adsorbents. Figure 8 As shown in (a), the pore size of fresh CS is mainly concentrated in 40-90nm, and the pore size of S5-CSMg5Fe5 and MC5-CSMg5Fe5 is mainly concentrated in 50-120nm, among which CS has the largest pore volume, while S5-CSMg5Fe5 and MC5-CSMg5Fe5 have a larger proportion of mesopores and macropores, which are formed because of the combustion of the biomass template during sample preparation. After 20 cycles, the pore size of CS and S5-CSMg5Fe5 is mainly concentrated in 20-50nm, and the pore size of MC5-CSMg5Fe5 is mainly concentrated in 30-70nm, among which MC5-CSMg5Fe5 has the largest pore volume. This shows that the doping of biomass template, MgO and FeC6H5O can increase the specific surface area and pore volume of S5-CSMg5Fe5 and MC5-CSMg5Fe5, thereby slowing down the sintering and agglomeration of calcium-based adsorbents during the carbonation / calcination cycle and increasing their stability during the cycle. Figure 8 (b) shows the N2 adsorption-desorption isotherms of CS, S5-CSMg5Fe5 and MC5-CSMg5Fe5. The N2 adsorption-desorption isotherms of all samples are type IV, indicating the presence of mesopores and macropores, and the hysteresis loops are H3 type, revealing that CaO particles agglomerate to form slit-like pores. After 20 carbonation / calcination cycles, the adsorption amount in the N2 adsorption-desorption isotherms of S5-CSMg5Fe5 and MC5-CSMg5Fe5 is significantly larger than that of fresh S5-CSMg5Fe5 and MC5-CSMg5Fe5, corresponding to the increase in pore volume after carbonation / calcination cycles.
[0070] Table 3 Pore structure parameters of calcium-based adsorbent before and after cycling
[0071]
[0072] 3.3 XPS analysis
[0073] In order to further investigate the situations of Fe, Mg and O in CS, S5-CSMg5Fe5 and MC5-CSMg5Fe5, XPS analysis of the three calcium-based adsorbents was carried out. Fig. 9 (a) is the wide scan XPS spectrum of C1s, Ca2p, O1s, Fe2p and Mg1s. Fig. 9 (b) is the XPS spectrum of Fe2p. 1 / 2 (724.69eV, 723.46eV) and Fe2p 3 / 2 (711.58eV, 710.97eV) two main peaks, indicating that Fe 3+ There are also two satellite peaks at (717.61eV, 717.92eV) and (732.31eV, 731.04eV), and the two smaller satellite peaks are adjacent to the two main peaks of Fe2p. Fig. 9 (c) is the XPS spectrum of Mg1s, which has an obvious characteristic peak at the electron binding energy (1303.98 eV, 1303.17 eV), corresponding to the electron binding energy of Mg element in MgO. Fig. 9 (d) is the XPS spectrum of O1s. It can be found that O1s has three peaks. The OⅠ peak (530.56eV, 530.40eV, 530.45eV) with lower binding energy is lattice oxygen, followed by the OⅡ peak (531.56eV, 531.47eV, 531.26eV) for surface chemical adsorption oxygen, and the OⅢ peak (532.61eV, 532.45eV, 532.37eV) with higher binding energy is dissociated oxygen. Among them, OⅡ is an important O species in the TCES system, because the concentration of OⅡ is positively correlated with the number of oxygen vacancies, and the more oxygen vacancies there are, the better the reactivity during the carbonation reaction. The maximum values of OⅡ peaks in S5-CSMg5Fe5 and MC5-CSMg5Fe5 (366.4561 and 430.3677) are 121.19% and 159.77% higher than those in CS (165.6743), respectively. This result shows that the doping of biomass template, MgO and FeC6H5O significantly increases the content of OⅡ, which is beneficial to the capture of CO2 by CaO during carbonation reaction. As can be seen from the figure, OⅡ is the main form of oxygen, and the concentration of OⅡ in S5-CSMg5Fe5 and MC5-CSMg5Fe5 is higher than that in CS, which indicates that there are more oxygen vacancies in S5-CSMg5Fe5 and MC5-CSMg5Fe5, and their oxygen mobility is also higher than that of CS, and Xn is higher during carbonation reaction.
[0074] 3.4 SEM and EDS analysis
[0075] The surface morphologies of different calcium-based adsorbents before and after carbonation / calcination cycles were investigated, e.g. Figure 1 shown. Figure 1 (a), (c) and (e) show that the prepared calcium-based adsorbent particles are relatively uniform. Fresh CS, S5-CSMg5Fe5 and MC5-CSMg5Fe5 all have developed porous structures. The pore structure of CS is mostly microporous, while S5-CSMg5Fe5 and MC5-CSMg5Fe5 are doped with biomass templates. After the biomass template is burned, a large number of medium and large pore structures are produced, which is consistent with the results measured by BJH. Some small-sized particles are also evenly attached to the surface of Figures (c) and (e), forming a certain pore structure. CS, S5-CSMg5Fe5 and MC5-CSMg5Fe5 after 20 carbonation / calcination cycles are shown in Figure 2. Figure 1 (b), (d) and (f), the three calcium-based adsorbents all underwent a certain degree of sintering, among which the surface sintering of CS was more serious than that of S5-CSMg5Fe5 and MC5-CSMg5Fe5. CS has undergone serious sintering and particle agglomeration, and the pores on the surface have been significantly reduced, leaving only a small amount of pores, which hinders the diffusion of CO2 inside the CS particles and reduces Xn during the carbonation reaction. While S5-CSMg5Fe5 presents a honeycomb shape combining large and small pores, MC5-CSMg5Fe5 presents an irregular structure combining large and small pores, and still has a relatively rich medium and large pore structure compared to CS, which has a positive effect on the energy storage performance of calcium-based adsorbents. Therefore, after 20 cycles, the Xn and Eg,n of S5-CSMg5Fe5 and MC5-CSMg5Fe5 are higher than those of CS.
[0076] Fig.10 The EDS mapping images of the elements Ca, Mg, O and Fe in the three calcium-based adsorbents, where green represents Ca, cyan represents Mg, red represents O, and purple represents Fe. It can be seen that the content of Mg and Fe in S5-CSMg5Fe5 and MC5-CSMg5Fe5 (Figures (b) and (c)) is significantly higher than that in CS (Figure (a)), and the Ca, O, Mg and Fe elements are evenly distributed on the particle surface, which indicates that various substances are well mixed in the calcium-based adsorbent, and also indicates that the generated MgO, MgFe2O4, Fe2O3 and Ca2Fe2O5 are evenly distributed on the surface of the calcium-based adsorbent, thereby inhibiting the agglomeration between CaO particles. This is consistent with the results of the SEM image, further confirming that the energy storage performance of S5-CSMg5Fe5 and MC5-CSMg5Fe5 is better than that of CS.
[0077] 4. Optical properties analysis
[0078] Fig.11 The absorption spectra of different calcium-based adsorbents at 300-1200nm were measured by ultraviolet spectrophotometry. The shaded part in the figure corresponds to the standard solar radiation spectrum (AM1.5) on the right axis. Since CS is pure white, its light absorption capacity for sunlight is obviously insufficient. After doping with FeC6H5O, it can be seen from XRD that Fe2O3 and Ca2Fe2O5 are generated during the high temperature process. The study shows that Fe metal oxides with cubic spinel structure can be used as narrow bandgap semiconductors and can absorb broadband solar radiation, thereby significantly increasing the light absorption capacity of calcium-based adsorbents doped with biomass templates, MgO and FeC6H5O, especially in the visible light band (300-650nm), and the light absorption rate increases with the increase of FeC6H5O doping content. At the same time, the energy in the visible light band accounts for about 50% of the total energy of solar radiation, so the utilization rate of solar energy by the doped calcium-based adsorbent has been significantly improved.
[0079] 5. Carbonation reaction kinetics analysis
[0080] The kinetic calculation results of CS, S5-CSMg5Fe5 and MC5-CSMg5Fe5 in the two reaction stages are shown in Table 4. The calculation results of the kinetic model are in good agreement with the fitting results, indicating that the grain model and the three-dimensional diffusion model can be used to analyze the two stages of the carbonation process. The reaction rate constants of different stages can be obtained from the slope, where kc1, kc10, kd1, and kd10 represent the reaction rate constants of the chemical reaction control stage and the diffusion control stage of the 1st and 10th cycles, respectively. It can be found that the reaction rate constant (kc) of the chemical reaction control stage is always greater than the reaction rate constant (kd) of the diffusion control stage, which is consistent with the rule that Xn increases rapidly at the beginning and then increases slowly.
[0081] Table 4 Reaction rate constants of CS, S5-CSMg5Fe5 and MC5-CSMg5Fe5
[0082]
[0083] Based on the particle model fitting reaction rate equation, the kinetic parameters of the carbonation reaction were calculated. Considering that the number of adsorbent samples tested by TG was small and it was difficult to determine the specific surface area of the adsorbent at the tenth cycle, only the kinetic parameters of CS, S5-CSMg5Fe5 and MC5-CSMg5Fe5 at the first cycle were calculated, as shown in Table 5.
[0084] Table 5 Carbonation reaction kinetic parameters of CS, S5-CSMg5Fe5 and MC5-CSMg5Fe5
[0085] Sample E(kJ / mol) <![CDATA[A(mol / (m 2 ·s))]]> CS 30.82 <![CDATA[8.62×10 -4 ]]> S5-CSMg5Fe5 21.01 <![CDATA[5.81×10 -4 ]]> MC5-CSMg5Fe5 24.30 <![CDATA[4.68×10 -4 ]]>
[0086] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of the present invention to be protected is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a novel calcium-based adsorbent, characterized in that: The following steps are involved: (1) drying the carbide slag in an oven at 80°C for 12 h to remove moisture from the sample, grinding the dried carbide slag into powder, and calcining it in a muffle furnace at 800°C for 1 h to obtain carbide slag powder; (2) Carbide slag powder, MgO powder and FeC6H5O powder were mixed and added into a ball mill, and ethanol was added as a dispersant for ball milling to fully mix the powders to obtain a sample; (3) Prepare a biomass solution and add the sample, mix on a magnetic stirrer, and then place in a convection oven at 80 °C for 20 h; (4) After drying, the mixture was ground into powder and calcined in a muffle furnace at 800°C for 1 h under air conditions; (5) The calcined sample was placed in a tubular furnace and pre-calcined at 800°C for 20 min under N2 conditions to obtain a calcium-based adsorbent.
2. The method for preparing the novel calcium-based adsorbent according to claim 1, characterized in that: In step (2), the ball mill rotates at a speed of 300 r / min for 30 min during ball milling.
3. The method for preparing the novel calcium-based adsorbent according to claim 1, characterized in that: In step (2), the mass ratio of the carbide slag powder, MgO powder and FeC6H5O powder is 100:5:
5.
4. The method for preparing the novel calcium-based adsorbent according to claim 1, characterized in that: In step (3), the concentration of the biomass solution is 5%-10%.
5. The method for preparing the novel calcium-based adsorbent according to claim 4, characterized in that: The biomass solution includes a soluble starch solution or a methylcellulose solution.
6. The method for preparing the novel calcium-based adsorbent according to claim 1, characterized in that: In step (3), during the stirring process of the magnetic stirrer, stirring is first performed at room temperature for 1.5 hours to allow the sample and the biomass solution to be fully mixed, and then heated and stirred to a semi-dry mixed state.
7. A novel calcium-based adsorbent prepared according to the method for preparing a novel calcium-based adsorbent according to any one of claims 1 to 6.
8. Use of the novel calcium-based adsorbent according to claim 7 in solar thermochemical energy storage.
9. The use according to claim 8, characterized in that: The calcium-based adsorbent is used to slow down sintering and enhance solar energy absorption capacity during the calcium circulation process, and is suitable for the thermochemical energy storage system of the third-generation solar thermal power station.